SPEECH ETIQUETTES RELATED TO ADDRESSING AND METHODS TO TRANSLATE THEM FROM ENGLISH TO TURKMEN - Saparmyradova Tumar Ishanberdiyevna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article focusses on speech etiquette related to forms of addressing and explores methods of translating them from English into Turkmen. Language is considered not only as a means of communication but also as a reflection of cultural values and social relationships. The study highlights the differences between English and Turkmen addressing systems. The article is based on communicative, contrastive, and translation-oriented teaching methodologies. It applies a comparative and pragmatic approach to demonstrate that literal translation of speech etiquette often leads to cultural misunderstanding. Therefore, the use of functional equivalence is essential to preserve the communicative meaning of expressions. The findings show that effective translation and teaching of speech etiquette require not only linguistic knowledge but also intercultural competence. The article concludes that addressing forms should be taught and translated with careful consideration of cultural context and social norms.